Pengaruh Diagram Venn dan Relasi dalam Meningkatkan Pemahaman Sistem Basis Data - Lin Suciani Astuti; Siti Julaeha (Universitas Indraprasta PGRI Jakarta, 2021)
This research aims to improve the understanding of database system learning using Venn diagrams and relation diagrams. The first stage of the research was by conducting a pretest that contained the material, questions, and solutions using the Venn diagram and the relation diagram. The post-test stage was in the same way so that it can be seen an increase in student understanding of the database system by using Venn diagrams and relations as tools. The primary object of this research is to increase students' understanding of the database system using Venn diagram operations and relation diagrams to solve database system questions. The method used was pre-experimental research with the design of one group pretest and post-test design. The samples used were 45 students in semester 5 of the Informatics Engineering Department for the 2020/2021 academic year of Indraprasta University PGRI. The instruments collected were in the form of pretest and post-test results. The percentage result (P) was that the pretest to post-test scores has increased from 64.33% to 86.33% based on the Venn diagram. The statistical hypothesis test using the Wilcoxon test obtained a sig value of 0.000 <0.05, which concluded that there was an increase between the pretest and post-test results based on the Venn diagram compared to the relation diagram. Therefore, the author describes that the average Unindra PGRI students in semester five can understand database questions by applying the Venn diagram material between relationships.